A multiple robot solution for urban reconnaissance. (3rd January 2011) - Janko, Balazs; Turner, Chris P.; Cave-Ayland, Kim S.; Pittuck, Martyn K.; Madgwick, Sebastian O.H.; Harwin, William S.
Coordinating aerial and ground based robotic platforms together with sensor payloads is described and some results are presented on the deployment of these robots in an urban environment for reconnaissance, in particular to find military threats. This work was done with the aim of competing in the UK MOD Grand Challenge competition in August 2008. This paper reviews the structure, control, coordination and integration of the robotic platforms for this event.